2021
DOI: 10.1111/jora.12654
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' Longitudinal School Engagement and Burnout Before and During COVID‐19—The Role of Socio‐Emotional Skills

Abstract: This longitudinal study examined school engagement and burnout profiles among early and middle adolescents before and during COVID‐19, and within‐class latent change and stability in students’ socio‐emotional skills the profiles. The longitudinal data were collected in fall 2019 and 2020 from 1381 5th to 6th, and 1374 7th to 8th grade students. Using repeated measures latent profile analyses based on school engagement and burnout we identified five study well‐being change profiles in both samples showing struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 47 publications
5
51
1
1
Order By: Relevance
“…Additionally, Salmela‐Aro et al. ( 2021 ) found that Finnish youth whose well‐being and academic engagement had decreased during the pandemic also experienced increased loneliness and a decreased sense of belonging. It will be important for future psychological research to explore methods of raising academic motivation in an entire generation of students, since this will be a crucial first step in getting academic development back on track.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Salmela‐Aro et al. ( 2021 ) found that Finnish youth whose well‐being and academic engagement had decreased during the pandemic also experienced increased loneliness and a decreased sense of belonging. It will be important for future psychological research to explore methods of raising academic motivation in an entire generation of students, since this will be a crucial first step in getting academic development back on track.…”
Section: Introductionmentioning
confidence: 99%
“…The implications of these changes for adolescent academic functioning and motivation were high on the political agenda in many countries. Findings from this special issue indicate that adolescents’ school bonding decreased from before to during the pandemic (Maiya, Dotterer, & Whiteman, 2021 ), and a substantial group of about 15% of adolescents reported a steeper decrease in academic well‐being, characterized by lower school engagement and higher burnout, than would be developmentally expected (Salmela‐Aro, Upadyaya, Vinni‐Laakso, & Hietajärvi, 2021 ). Moreover, adolescents’ academic motivation was lower on online compared to physical school days during the pandemic (Klootwijk et al., 2021 ), suggesting that the effects could be attributed to the restrictive measures rather than the pandemic more broadly.…”
Section: Academic Functioning During the Pandemicmentioning
confidence: 99%
“…Again, results showed that not all adolescents were affected equally by the pandemic (Salmela‐Aro et al., 2021 ). Adolescents who experienced more stress or whose family experienced more pandemic‐related financial need were at higher risk for declined school bonding, whereas adolescents with better coping or whose parents were more involved in education reported weaker declines in school bonding (Maiya et al., 2021 ).…”
Section: Academic Functioning During the Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study examined latent profiles of stress among Finnish school principals during an unprecedented time of global COVID-19 pandemic, when in many countries lockdowns, school closures, and social distancing took place, resulting as increased levels of stress, anxiety, and loneliness among students ( Bu et al, 2020 ; Zheng et al, 2021 ), which had detrimental effects on some students’ well-being ( Loades et al, 2020 ; Salmela-Aro et al, 2021 ). Teachers and school principals were forced to engage in a dramatically different way, and shift from in-person to remote work ( Weiner et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%